BASIC PROBLEMS IN LEGAL REGULATION OF DIGITAL ASSETS: EXAMPLES IN THE USA, EU AND SERBIA - Nikolić, Ljubica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Modern financial technologies (Financial Technologies - FinTech) have improved traditional finance, while at the same time building a fundamentally new financial alternative. The application of FinTech has created digital financial products that are legally regulated, however, many crypto products remain outside the law. The cryptocurrency market is a digital decentralized system that operates according to its own rules that users voluntarily accept, using personalized digital transactions. The application of FinTech in banking represents a legal activity of banks with the aim of strengthening competitive advantages in providing financial services, while part of the digital improvements are required by central banks. In contrast, Blockchain technology has created a digital financial alternative, which, by using the Internet and sharing original digital records, between networked users around the world, allows individuals to directly manage their digital wallets via phones and computers, without centralized control and outside of banking systems. In the initial period of application, Blockchain technology created resistance and was ignored by state regulatory bodies, but after several years of application, the process of legal regulation of digital products and markets that were created on the basis of Blockchain and other digital technologies began. Legal regulation of already developed and widely used digital markets and assets is the topic of this paper, with special attention to legal solutions in this area in the USA, the EU and Serbia. The challenges of legal regulation of digital assets are numerous, from insufficient knowledge of digital technologies to the impossibility of legal norming of decentralized digital segments. It is necessary that the creators of law, as well as the persons who apply it, have basic knowledge of modern digital technologies.
Keywords: Digital Technologies; Digital Assets; Decentralized Finance; Legal Regulation; Challenges